Common and rare TBK1 variants in early-onset Alzheimer disease in a European cohort - Verheijen, Jan; van der Zee, Julie; Gijselinck, Ilse; Van den Bossche, Tobi; Dillen, Lubina; Heeman, Bavo; Gómez-Tortosa, Estrella; Lladó, Albert; Sanchez-Valle, Raquel; Graff, Caroline; Pastor, Pau; Pastor, Maria A; et al. (Neurobiology of aging, 2018)
TANK-binding kinase 1 (TBK1) loss-of-function (LoF) mutations are known to cause frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS), often combined with memory deficits early in the disease course. We performed targeted resequencing of TBK1 in 1253 early onset Alzheimer's disease (EOAD) patients from 8 European countries to investigate whether pathogenic TBK1 mutations are enriched among patients with clinical diagnosis of EOAD. Variant frequencies were compared against 2117 origin-matched controls. We identified only 1 LoF mutation (p.Thr79del) in a patient clinically diagnosed with Alzheimer's disease and a positive family history of ALS. We did not observe enrichment of rare variants in EOAD patients compared to controls, nor of rare variants affecting NFκB induction. Of 3 common coding variants, rs7486100 showed evidence of association (OR 1.46 [95% CI 1.13-1.9]; p-value 0.01). Homozygous carriers of the risk allele showed reduced expression of TBK1 (p-value 0.03). Our findings are not indicative of a significant role for TBK1 mutations in EOAD. The association between common variants in TBK1, disease risk and reduced TBK1 expression warrants follow-up in FTD/ALS cohorts.
Keywords: heterozygot; genetické asociační studie; protein-serin-threoninkinasy; kohortové studie; homozygot; Male; Heterozygote; genetická variace; Cohort Studies; mutace ztráty funkce; Genetic Association Studies; Protein Serine-Threonine Kinases; Loss of Function Mutation; Europe; Alzheimerova nemoc; Alzheimer Disease; Aged; mužské pohlaví; senioři; Frontotemporal Dementia; Homozygote; Evropa; Amyotrophic Lateral Sclerosis; frontotemporální demence; lidé; ženské pohlaví; Humans; Risk; Alleles; Genetic Variation; Female; riziko; alely; lidé středního věku; amyotrofická laterální skleróza; Middle Aged